Lentil Biorooting Agents: An Ecological Alternative to Improve the Growth and Development of Italian Zucchini in Sustainable Production Systems - Uriel González-Lemus; Félix Antonio Tapia-Zayago; Sergio Rubén Pérez-Ríos; Ana Karen Zaldívar-Ortega; Edgar Omar Rueda-Puente; Aracely Hernández-Pérez; Lucio González-Montiel; Iridiam Hernández-Soto (Horticulturae)
Zucchini (Cucurbita pepo L.) is a crop of global economic importance. Therefore, there has been a continuous search for alternative cultivation methods that contribute to improving its growth and development. In the context of sustainable agriculture, plant protection techniques involve the use of substances of natural origin (e.g., biorooters), which have a positive impact on the production cycle of plants. In this study, the effects of a lentil biorooter on the growth and development of Italian zucchini were investigated. Five treatments were analyzed in the study: 25 (T1), 50 (T2) and 75 (T3) mL of the biorooter; a chemical rooting agent (“Raixen PLUS ©”; T4); and a control (T0). The results showed that the application of the lentil biorooter (T3) increased the plant height by 166%, the number of leaves by 113%, the aerial fresh weight by 169%, the root length by 165%, the fresh and dry root weights by 102% and 116%, and the number of flowers and female flowers by 89% and 177%, respectively, compared to the control (T0). In the case of the conventional rooting agent “Raixen PLUS ©” T4, compared to (T3), the following agro-nomic variables were reduced: plant height by 13%; the number of leaves by 124%; fresh and dry aerial weight by 103% and 107%, respectively; fresh and dry root weight by 9% and 117%, respectively; and the number of total and female flowers by 112% and 160%, respectively. Pearson correlation coefficients were calculated to compare the heights of the plant between the five treatments, as well as to compare the number of leaves to the fresh aerial weight and the length of the root to its fresh weight. Furthermore, the principal component analysis (PCA) results indicated that the differences between components 1 and 2 appeared to be positively influenced by the root length. These results suggest that lentil biorooters could be an ecological alternative to conventional rooters, thus mitigating the adverse effects of their use in zucchini crop production. This is the first study to report on the induction of growth and development using a lentil biorooter in zucchini.